Fetal Umbilical Artery Velocimetry Indices and Pregnancy Outcome Among Preeclamptic Women at the Federal Teaching Hospital, Abakaliki, Southeast Nigeria - MAMAH, JOHNBOSCO; ONOH, ROBISON; ORJI, MICHEAL; DARLINTON-PETER CHIBUZOR, UGOJI; OTU, Chichetaram; Umeora, Odidika (International Journal of Innovative Research in Medical Science, 2023)
An accurate tool to identify fetuses at risk of in-utero compromise in women with Preeclampsia is unknown. We studied the hemodynamic changes in the fetal umbilical and middle cerebral arteries and their association with pregnancy outcomes. This was a cross-sectional study among eligible pregnant women with Preeclampsia. We conducted a Doppler evaluation of the fetal umbilical and middle cerebral artery indices. The neonatal APGAR scores, birth weight, NICU admission and perinatal deaths were documented. Maternal complications were documented. Data analysis was undertaken with Statistical Package for Social Sciences (IBM-SPSS, version 22, Chicago II, USA). Means were compared using the Z-test for continuous variables, while categorical variables were compared with Chi-square. Relationships were assessed using Pearson's correlation, with significance at P< 0.05. The accuracy of Doppler indices was calculated using contingency tables. There was a statistically significant association between fetal complications and Doppler indices but not with maternal complications. The Sensitivity of Doppler indices was higher with fetal umbilical artery Doppler indices, while the middle cerebral artery indices were more specific. Accuracy is better when Doppler indices are combined with the cerebro-placental ratio. In women with normal Doppler indices, the indices decreased with advancing gestational age, but values were higher when compared with nomograms. In conclusion, we found an association between fetal Doppler indices of the umbilical artery and adverse fetal outcomes. Abnormal umbilical artery Doppler indices suggest fetal compromise, while normal middle cerebral artery Doppler is reassuring.